2018
DOI: 10.1371/journal.pmed.1002660
|View full text |Cite
|
Sign up to set email alerts
|

Nilvadipine in mild to moderate Alzheimer disease: A randomised controlled trial

Abstract: BackgroundThis study reports the findings of the first large-scale Phase III investigator-driven clinical trial to slow the rate of cognitive decline in Alzheimer disease with a dihydropyridine (DHP) calcium channel blocker, nilvadipine. Nilvadipine, licensed to treat hypertension, reduces amyloid production, increases regional cerebral blood flow, and has demonstrated anti-inflammatory and anti-tau activity in preclinical studies, properties that could have disease-modifying effects for Alzheimer disease. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 136 publications
(107 citation statements)
references
References 27 publications
2
103
0
Order By: Relevance
“…The study failed to demonstrate any effect of nilvadipine on the cognitive outcome. However, in predefined subgroup analyses, there was less cognitive decline in patients with MMSE >20, in males and in APOE ε4 carriers [97]. As found in the aforementioned casereport, a subgroup of patients in the NILVAD trial showed an increase of cerebral blood flow in hippocampal regions [98].…”
Section: Clinical Studiesmentioning
confidence: 53%
“…The study failed to demonstrate any effect of nilvadipine on the cognitive outcome. However, in predefined subgroup analyses, there was less cognitive decline in patients with MMSE >20, in males and in APOE ε4 carriers [97]. As found in the aforementioned casereport, a subgroup of patients in the NILVAD trial showed an increase of cerebral blood flow in hippocampal regions [98].…”
Section: Clinical Studiesmentioning
confidence: 53%
“…The ADAS-Cog can be used to distinguish AD from normal aging (for example, 12 points have been designated to denote AD, with a sensitivity and specificity ≥94% by Nogueira et al,10 points for AD, with the sensitivity of 84% and specificity of 91% by Jemma et al), 18,20 as well as to assess the severity of AD 22,23 and the efficacy of antidementia treatment. 24,25 In addition, ADAS-Cog can also be used to discriminate AD from depression 19 and vascular dementia. 26 However, the discriminative power of this scale in the MCI population is controversial.…”
mentioning
confidence: 99%
“…Although Aβ, p-tau, and t-tau in the CSF have been reported to be useful as disease progression markers 41, 44 , there is still little evidence for their causal relationship with LOAD in randomized clinical trials (RCTs) 45, 46 . Recent RCTs on the elimination of the accumulated Aβ or tau proteins could not provide solid evidence for improvement of the symptoms of LOAD 4749 . While clinical trials with small sample sizes have shown that eliminating the Aβ elements led to symptomatic improvement 50 , larger studies have failed to establish consistent results 47, 51, 52 .…”
Section: Discussionmentioning
confidence: 99%